Practical rules for graphic presentation of business statistics - Smart, L.Edwin.; Arnold, Sam. (Ohio The Bureau of Business Research, 1951)
The aim of this publication is to present in a clear and concise manner the essential rules for correct construction of the most widely used types of business charts.
Includes Bibliographical references and index
osc 18/7/16
Loans
Keywords: Statistical Methods; Business statistics; Business statistics - graph